Peoples' participation in administration: a conceptual framework - Nanda, Debidas (2005)
Peoples' participation in development represents a process by which goals are set and means are chosen in relation to all sorts of developmental issues. The assumption is that, through participation, the goals of the society are set in a way so as to maximize the distribution of benefits in the society to match the needs and desires of the people. The article examines various models of peoples' participation in development process where people are deemed to be the target group in the society. - Reproduced.
Keywords: Peoples participation; Workers participation